Breeding Season Movements and Dispersal of Northern Bobwhites in Fragmented Habitats of Virginia - Michael L. Fies; K. Marc Puckett; Bonnie Larson-Brogdon (National Quail Symposium Proceedings, 2017)
To better understand dispersal patterns of northern bobwhites (Colinus virginianus) in fragmented habitats, we measured breeding season movements of 198 radiomarked bobwhites in central and eastern Virginia during 1994–1996. Mean distance between arithmetic centers of winter (1 Feb–15 Apr) and early breeding season (16 Apr–30 Jun) activity areas was 1,194 +- 137 m. Distance between centers of winter and late breeding season (1 Jul–15 Sep) activity areas averaged 1,644 +- 209 m and was greater for juveniles than adults (P = 0.04). Maximum distances moved between winter and breeding season locations (early, late, and combined) was also greater for juveniles than adults (P <= 0.05). Forty-nine of 198 (25%) bobwhites dispersed more than 2 km. A greater proportion of juveniles (28%) than adults (10%) dispersed > 2 km. Juvenile males were more likely to disperse than any other sex/age group (P = 0.02). Adult males were least likely to disperse (P < 0.01). We suggest that breeding season movements of bobwhites may be greater in fragmented landscapes than in areas with large blocks of suitable habitat. We recommend that researchers utilize dispersal information to help define the spatial distribution of habitat patches necessary to perpetuate bobwhite populations at a regional level.
Keywords: breeding season; Colinus virginianus; dispersal; habitat fragmentation; metapopulations; movements; northern bobwhite; Virginia